Investigations and calculations into decreasing the uncertainty of a nanopositioning and nanomeasuring machine (NPM-Machine) - Schmidt, Ingomar; Hausotte, Tino; Gerhardt, Uwe; Manske, Eberhard; Jäger, Gerd (Institute of Physics: Hybrid Open Access, 2007)
Continuously increasing demands on nanopositioning and nanomeasuring (NPM) machines require a detailed analysis of and a decrease in measurement uncertainty. Initial studies have been done in the field of length and angle measurement. The analysis resulted in updated assemblies, which were investigated further. Significant improvements in mechanical stability, drift behaviour and temperature dependence were produced. To minimize the undesired heat production by the non-self-locking vertical linear drive systems, an improved weight force compensation arrangement adaptable to different object masses was developed and tested. Also, the system's natural frequencies were analysed. A modified structure with increased stiffness of the vertical drive system was designed to improve the NPM's dynamic behaviour.
Keywords: nanopositioning and nanomeasuring machine; laser interferometer; angle sensor; weight force compensation